Rationality [compact disc, unabridged] : what it is, why it seems scarce, why it matters - Pinker, Steven, 1954- (Penguin Audio, 2021)
"In the 21st century, humanity is reaching new heights of scientific understanding--and at the same time appears to be losing its mind. How can a species that sequenced the genome and detected the Big Bang produce so much fake news, quack cures, conspiracy theories, and "post-truth" rhetoric? A big part of Rationality is to explain these tools--to inspire an intuitive understanding of the benchmarks of rationality, so you can understand the basics of logic, critical thinking, probability, correlation and causation, the optimal ways to adjust our beliefs and commit to decisions with uncertain evidence, and the yardsticks for making rational choices alone and with others"--